The Role of Muhammadiyah Organization in Indonesia Education Reform on 1912-1923 - Fitria Eka Imsawati; Bambang Soepeno; Kayan Swastika (History Education, University of Jember, 2020)
Muhammadiyah is an organization that makes their movement on socio-religious reform. Muhammadiyah is supported by society as a non-political organization that concerns about charity and education. Muhammadiyah always conducts reform in every aspects especially in education. The problem in this research is how was the education system in Indonesia right before Muhammadiyah was founded, how were the effort and action that Muhammadiyah did at that time on the reform of education and it’s effects. The purpose of this research is to describe about the role of Muhammadiyah in the reform of the education in 1912-1923. The research method used in this research is historical research method with educational sociology approach and open system organizational theory. The benefit of this research is to be expected to add the knowledge and information about Muhammadiyah and as a source of learning about that organization. The other benefit is this research can be used as a source for the other similar researches on the future. The first conclusion of this research is education system in Indonesia right before Muhammadiyah was founded, educational secularism, and Islamic educational traditionalism. The second conclusion is the attempt and action that Muhammadiyah did at that time on the reform of education was the implementation of principal of education, the combination of western and traditional education in the education that was conducted Muhammadiyah. The last conclusion is the effect of reform in education conducted by Muhammadiyah on the society namely integralistics and contextual teaching and learning model and arose of the modern figures like KH. Abdul Razzaq Fachruddin, H. Abdul Malik Karim Amrullah (HAMKA), and M. Rasjidi. Keywords: role, Muhammadiyah Organization, education reform